Imagination in Martha Nussbaum and Kant - Herszenbaun, Miguel (ARFIL y UNL, 2021)
In her book Poetic Justice, Martha Nussbaum supports the thesis that the imagination plays a major role in the judicial decision-making. In this paper, I intend to defend that Nussbaum’s thesis is partially Kantian. However, by analyzing in detail how the imagination works in Kant and in Nussbaum, I will be able to show the main differences and similarities. I claim that the main problem that Nussbaum’s imagination is thought to solve is the articulation between singular and universal. This is done by means of a faculty capable of connecting with the emotional aspect of the human being.